Tính phổ biến của phương thức lặp trong loại hình học ngôn ngữ dưới góc độ ngôn ngữ học tri nhận. /Ngô Thị Huệ. - Ngô, Thị Huệ.
This article studies the universality of reduplication in terms of Linguistic typology from a new cognitive perspective. The iconicity of sound form and the meaning, especially the principle that “complicated forms indicate complicated meaning” is adopted to explain the cognitive motivation of inflectional reduplication. It is believed that the cognitive iconicity is the motivation of the universality of inflectional reduplication.